PEMBUATAN DAN KARAKTERISASI GENTENG POLIMER MENGGUNAKAN BAHAN LIMBAH INDUSTRI KARET SHEET DAN POLIPREPILEN BEKAS DENGAN CAMPURAN AGREGAT PASIR HALUS DAN ASPAL - nur aisyah tambak (Saintia Fisika, 2013)
Fabrication and characterization of polymer roof materials had been done made of mixture of rubber waste used polypropylene, sand, asphalt and epoxy. With a mixture of sand and rubber variation as independent variables with composition are (30:20)gr, (32,5:17,5:)gr, (35:15)gr, (37,5:12,5)gr, (40:10:)gr, (42,5:7,5)gr , (45:5)gr and (47,5:2,5)gr. Then added with 15 gr of epoxy, 5 gr of asphalt and 30 gr of used polypropylene. Properties of roof observed include porosity, water absorption, impact and flexural strength test. The results of this study showed that the optimum mix is a mixture of variation (35:15)gr which provides water absorption and good mechanical with the addition of 5 gr asphalt as water retention. Key words: polymer roof, rubber waste, polypropylene